Plate-like nanoparticles, compositions thereof, and formation thereof

By using metal nanoparticle compositions containing plate-like nanoparticles, the problems of high cost and high eutectic melting point in traditional welding materials are solved, and a stronger and higher performance bulk metal matrix is ​​achieved.

CN119546400APending Publication Date: 2025-02-28KUPRION INC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202380052744.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-24
Filing Date
2023-06-22
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Among the existing solder materials, traditional lead-based solder is gradually phased out, and its substitutes such as Sn/Ag/Cu systems have problems such as high cost, high eutectic melting point and whisker growth, which are difficult to effectively use in some applications.

Method used

Using a metal nanoparticle composition containing plate-shaped nanoparticles, a significant amount of plate-shaped nanoparticles is generated by adjusting the synthesis conditions, thereby improving the bulk density and consolidation performance of the metal nanoparticles.

Benefits of technology

A stronger block metal matrix is ​​achieved, which reduces porosity, improves electrical and thermal conductivity, and manufactures block metal matrix at lower processing temperatures, reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119546400A_ABST
    Figure CN119546400A_ABST
Patent Text Reader

Abstract

The metal nanoparticles may grow under conditions that promote the formation of plate-like nanoparticles having a surfactant coating thereon. Such conditions may include slow metal salt reduction and slow cooling after formation of the metal nanoparticles. The plate-like nanoparticles have a fusion temperature substantially lower than the melting point of the corresponding bulk metal and form a robust structure when subjected to consolidation with each other. A composition may include a plurality of metal nanoparticles having a surfactant coating thereon, where at least about 20% of the metal nanoparticles are plate-like nanoparticles, and the surfactant coating includes at least one surfactant. The composition may also include different amounts of substantially spherical metal nanoparticles. The metal nanoparticles may be formulated as nanoparticle paste compositions, sprayable formulations, and inks that may facilitate dispensing and consolidation of the metal nanoparticles.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] Although lead has traditionally been used in many industrial applications, current regulations have required the elimination and / or phasing out of lead in most commercial products. Soldering applications, particularly in electronics and vehicle manufacturing, have been severely affected by lead bans. Many alternatives to traditional lead-based solders have been developed, with the Sn / Ag / Cu (SAC) system being the most widely used, but many have exhibited disadvantages that make them unsuitable for use in certain applications, such as excessive expense (each weight % of silver added roughly doubles the cost, and tin is also expensive), high eutectic melting points, and potential whisker growth for tin-based solders containing high percentages of tin.

[0002] Compositions containing metal nanoparticles are beginning to be used as substitutes for traditional soldering materials. Such compositions are increasingly referred to as sintered metal systems. Metal nanoparticles having a size of about 100 nm or less, particularly metal nanoparticles having a size of about 20 nm or less, can exhibit a significant reduction in melting point compared to corresponding bulk metals, thereby allowing metal nanoparticles to be pseudo-liquefied and consolidated at temperatures comparable to traditional soldering materials. For example, due to the high thermal and electrical conductivity of spherical copper nanoparticles and the relatively low cost of copper, the metal has been extensively studied as an alternative soldering material. Once metal consolidation occurs at or above the fusion temperature, the melting point of the resulting metal matrix is ​​restored to a value close to the melting point of the corresponding bulk metal, thereby allowing the appropriate operating conditions of the consolidated metal nanoparticles to be based on the melting point of the bulk metal, rather than on the much lower fusion temperature of the metal nanoparticles.

[0003] Many methods for producing substantially spherical metal nanoparticles within a target particle size range with a narrow particle size distribution have been developed, typically by using a surfactant to control the nucleation and growth rate of the metal nanoparticles. Although compositions containing substantially spherical metal nanoparticles are suitable for many applications, considerable care may be required to produce a strong metal matrix during consolidation, particularly, for example, when the metal matrix needs to bear a mechanical load or is subjected to mechanical stress. Without being bound by theory or mechanism, when a bulk metal matrix is ​​produced after consolidating substantially spherical metal nanoparticles, the void volume in the closely packed or nearly closely packed metal spheres can lead to excessive porosity. When the consolidation of the metal nanoparticles occurs to form a bulk metal state, the void volume can also be produced by the gradual hardening of the metal matrix. Therefore, the looser the initial stacking state of the metal nanoparticles, the higher the porosity of the resulting bulk metal state. Using substantially spherical metal nanoparticles with a bimodal particle size distribution can solve this difficulty to a certain extent by promoting a higher packing density before the metal nanoparticles undergo consolidation with each other.

[0004] In addition to welding applications, it has been proposed that metal nanoparticles are used in many other fields, including but not limited to communications, electronics and medical applications. Silver nanoparticles and gold nanoparticles have been widely used for these purposes. The effective consolidation of substantially spherical metal nanoparticles remains challenging in these fields and many other fields. For example, silver nanoparticles may require heating up to 1 hour to promote effective consolidation, and may need to apply pressure to achieve acceptable density, electrical conductivity and thermal conductivity in the resulting bulk metal. For high temperature applications in electric fields, the migration of silver may cause problems. In addition, the high material cost of noble metal systems also remains challenging. For example, gold nanoparticles are very expensive for most applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0005] The following drawings are included to illustrate certain aspects of the present disclosure and should not be considered exclusive embodiments. The disclosed subject matter is capable of considerable modification, alteration, combination, and equivalents in form and function as will occur to those of ordinary skill in the art and having the benefit of this disclosure.

[0006] Figure 1 and Figure 2 is a diagram of the putative structure of a substantially spherical metal nanoparticle having a surfactant coating thereon.

[0007] Figure 3 is a diagram of the putative structure of a platelet nanoparticle having a surfactant coating thereon.

[0008] Figure 4 is a diagram showing substantially spherical metal nanoparticles in a close-packed configuration.

[0009] Figure 5 It is a diagram showing plate-like nanoparticles with overlapping and stacked structures.

[0010] Figure 6 is a diagram showing how plate-like nanoparticles can undergo stacking and consolidation with each other.

[0011] Figure 7 is a bar graph of the particle size distribution obtained from a representative copper nanoparticle synthesis in which plate-like nanoparticles were produced.

[0012] FIG. 8A to FIG. 8D are exemplary SEM images of copper nanoparticles produced at different reducing agent introduction rates.

[0013] Fig. 9 is an exemplary SEM image of a bulk copper matrix formed upon sintering copper nanoparticles that are primarily plate-shaped nanoparticles.

[0014] FIG. 10A to FIG. 10Care illustrative photographs of thin films formed from various types of copper nanoparticles after sintering. DETAILED DESCRIPTION

[0015] The present disclosure relates generally to metal nanoparticles, and more particularly to metal nanoparticle compositions comprising plate-like nanoparticles and the formation and use thereof.

[0016] As described above, substantially spherical metal nanoparticles, such as copper nanoparticles, can be consolidated to form a bulk metal matrix. However, when consolidating substantially spherical copper nanoparticles, great care may be required to form a solid bulk metal matrix, including applying pressure in some cases to achieve a suitable density.

[0017] The present disclosure provides a composition comprising metal nanoparticles, wherein at least a portion of the metal nanoparticles are plate-like nanoparticles (i.e., the metal nanoparticles have a plate-like morphology, rather than a substantially spherical shape). At least about 20% of the metal nanoparticles in the composition (and often more) can contain the plate-like nanoparticles in the composition described herein. Surprisingly, several simultaneous changes in the synthesis conditions for producing substantially spherical metal nanoparticles can provide a composition containing a significant amount of plate-like nanoparticles, as further discussed herein. Although substantially spherical metal nanoparticles can be produced by quickly introducing a reducing agent (e.g., an addition time of 1-2 minutes) into a solution containing a metal salt and one or more surfactants, adding the reducing agent to the solution more slowly and maintaining the reaction medium at a controlled temperature, sometimes without applying additional heat thereto, can provide at least partially formed plate-like nanoparticles. Slow cooling of the reaction medium can further help promote the formation of plate-like nanoparticles. In various cases, plate-like nanoparticles can be formed in combination with substantially spherical metal nanoparticles, wherein, depending on the synthesis conditions, the plate-like nanoparticles can be present in larger or smaller amounts than substantially spherical metal nanoparticles. The ratio between substantially spherical metal nanoparticles and plate-like nanoparticles can be further adjusted by adjusting additional components present in the reaction medium in which the metal nanoparticle formation occurs. For example, the type and amount of surfactant in the organic solvent in which the metal nanoparticle formation occurs can further affect the type of metal nanoparticles formed.

[0018] There is a natural limit to the packing density of spheres in three-dimensional space. For single-size spheres, theory predicts that an ideal cubic close packing or hexagonal close packing structure effectively fills about 74% by volume (26% void volume). When metal nanoparticles with two different sizes are stacked (the diameter ratio of the larger metal nanoparticles to the smaller metal nanoparticles is about 10:1), the packing density can be increased to about 87% (13% void volume). Random stacking arrangement provides significantly larger void volume (about 36%), which is usually the arrangement found when metal nanoparticles are deposited on the surface. Due to these characteristics, it may be problematic to form a solid bulk metal matrix from substantially spherical metal nanoparticles.

[0019] Compositions comprising plate-like nanoparticles, preferably comprising plate-like nanoparticles as at least a major portion of the metal nanoparticles in the composition, can provide a more solid bulk metal matrix when undergoing metal nanoparticle consolidation. A packing efficiency greater than 90% (less than 10% void volume) can be achieved to produce a metal matrix (e.g., in a film, a solder-like joint, an injection molded component, etc.) that is denser than when substantially spherical metal nanoparticles are consolidated alone. The packing efficiency can be further improved when aging, thermal shock and / or thermal cycling occur. Without being bound by theory or mechanism, it is believed that the plate-like nanoparticles provide a denser packing before the consolidation of the metal nanoparticles, and the layer-by-layer stacking of the plate-like particles promotes a denser packing, thereby resulting in a bulk metal matrix with fewer pores (denser) after consolidation. Therefore, a higher degree of long-range integrity can be achieved in the bulk metal matrix produced by the consolidation of the metal nanoparticles. Contrary to the behavior of substantially spherical metal nanoparticles, these benefits can also be achieved when consolidation occurs even when little or no external pressure is applied. The conductivity values ​​achieved when consolidating metal nanoparticles containing a significant amount of plate-like nanoparticles can approach the conductivity values ​​of bulk metal structures produced, for example, by techniques such as casting or electroplating. At least, the conductivity achieved when consolidating plate-like nanoparticles can exceed the conductivity of bulk metal structures produced when only substantially spherical metal nanoparticles are consolidated.

[0020] In addition to the benefits provided by the plate-like nanoparticles themselves, compositions containing a significant amount of plate-like nanoparticles can be formulated as nanoparticle pastes, which can further promote the rapid consolidation of metal nanoparticles as a dense bulk metal matrix, as well as the rapid distribution of metal nanoparticles. Sprayable formulations and inks containing plate-like nanoparticles can also be prepared and provide similar benefits. In addition, when solvents and other volatiles are removed from compositions containing plate-like nanoparticles, the plate-like nanoparticles can be further pulled together when the plate-like nanoparticles undergo consolidation, thereby further improving the stacking efficiency.

[0021] Once the metal nanoparticles have been processed into a bulk metal matrix, the bulk metal matrix can remain stable until the temperature close to the melting point of the corresponding bulk metal. Therefore, the metal nanoparticles and the nanoparticle pastes comprising the metal nanoparticles can allow initial processing to be carried out at a relatively low temperature (~180-240 ° C or lower, depending on the size of the metal, the metal nanoparticles and the ratio of the plate-like nanoparticles to the substantially spherical metal nanoparticles), and then be conducive to use at a much higher operating temperature. Low initial processing conditions are advantageously compatible with a series of substrate materials and processing conditions for forming integrated circuits and other electronic materials, which can constitute a non-limiting type of application of the metal nanoparticles described herein. Such processing conditions can be similar to those used in traditional welding applications.

[0022] Copper can be an ideal metal for forming metal nanoparticles, such as metal nanoparticles containing a significant amount of plate-like nanoparticles as described herein, due to the metal's low cost and high electrical and thermal conductivity values. Additional disclosure regarding copper nanoparticles and their synthesis is provided below.

[0023] Before discussing the embodiments of the present disclosure in more detail, a brief description of metal nanoparticles and metal nanoparticle pastes will first be provided, wherein copper nanoparticles are representative examples of such metal nanoparticles, so that the rest of the disclosure can be better understood. Metal nanoparticles exhibit many properties that can be significantly different from the corresponding bulk metal. One particularly important property of metal nanoparticles is the fusion or consolidation of nanoparticles that occurs at the fusion temperature of the metal nanoparticles. As used herein, the term "fusion temperature" refers to the temperature at which the metal nanoparticles appear to liquefy to produce a molten appearance. As used herein, the terms "fusion" and "consolidation" synonymously refer to a bulk metal matrix, such as a bulk copper matrix, in which metal nanoparticles agglomerate or partially agglomerate with each other at or above the fusion temperature to form a larger block (sintered block). The bulk metal matrix can take various forms, such as a thin film, an electrical or thermal connection between two surfaces, an interconnect, a solder joint, or a larger bulk metal block. The morphology of the bulk metal matrix can be affected by the amount of plate-like nanoparticles present in combination with substantially spherical metal nanoparticles, as described in further detail herein.

[0024] When the size is reduced, especially in the case of substantially spherical metal nanoparticles, the temperature at which the metal nanoparticles appear to liquefy drops sharply from the temperature of the corresponding bulk metal when the equivalent spherical diameter is less than about 20nm. For example, compared with the melting point of bulk copper at 1084°C, substantially spherical copper nanoparticles within a suitable size range can have a fusion temperature of about 240°C or less, or about 220°C or less, or about 200°C or less. Both substantially spherical metal nanoparticles and plate-like nanoparticles can exhibit this type of reduced fusion temperature. For example, plate-like nanoparticles containing copper and having a particle size as described herein can exhibit a fusion temperature of about 180°C to about 240°C, or about 200°C to about 240°C, or about 220°C to about 240°C, which can be only slightly different from the fusion temperature of substantially spherical metal nanoparticles. Without being bound by theory, it is believed that due to the lower thermodynamic stability of plate-like nanoparticles, plate-like nanoparticles can exhibit a lower fusion temperature than substantially spherical metal nanoparticles at larger particle sizes, as further discussed below. When the metal nanoparticles are consolidated at or above the fusion temperature, a bulk metal matrix can be produced at significantly lower processing temperatures than when processing directly with the bulk metal itself as the starting material. Once the bulk metal matrix has been formed from the metal nanoparticles, the melting point is close to that of the bulk metal itself and the bulk metal matrix contains multiple grain boundaries.

[0025] Compared with spherical nanoparticles of comparable size, plate-like nanoparticles have a higher surface area, thereby providing higher contact between other plate-like nanoparticles to promote consolidation into a bulk metal matrix. Advantageously, the plate-like nanoparticles of the present disclosure can lead to a reduction in the formation of such grain boundaries in a bulk metal matrix. Once the plate-like nanoparticles have been consolidated together, the reduction in grain boundary formation can be converted into improved electrical and thermal properties. The reduction in grain boundary formation may be due to the tendency of stacked plate-like nanoparticles to merge into larger crystalline phases, rather than the tendency of multiple contact points to produce a large number of grain boundaries that occur in the case of substantially spherical metal nanoparticles. The tendency of plate-like nanoparticles to merge into larger crystalline phases is believed to be due to the atomically flat surfaces of plate-like nanoparticles and the easy alignment of the lattices therein when the plate-like nanoparticles are stacked on each other. In contrast, substantially spherical metal nanoparticles can undergo an energy-unfavorable rearrangement to form a polycrystalline phase with multiple grain boundaries. For example, when observed in an SEM image, when at least a portion of their upper or lower surfaces is shown as being substantially flat, the plate-like nanoparticles can be considered to be atomically flat. In some cases, the thickness of a plate-like nanoparticle can vary in a step-like manner, where various portions of the plate-like nanoparticle are atomically flat before suddenly transitioning to another atomically flat portion. That is, in some cases, a plate-like nanoparticle can have different through-plane thicknesses at different locations thereon.

[0026] Another aspect related to the atomically flat surfaces of plate-like nanoparticles is that they have a higher reactivity than metal nanoparticles of comparable size that are substantially spherical in shape. Without being bound by theory or mechanism, it is believed that the higher reactivity is due to the lower thermodynamic stability of plate-like nanoparticles compared to substantially spherical metal nanoparticles. Therefore, plate-like nanoparticles can display characteristic metal nanoparticle properties (e.g., low fusion temperature) above a particle size threshold at which these properties begin to disappear in substantially spherical metal nanoparticles.

[0027] Although the relatively high reactivity of platelet nanoparticles may be desirable in many cases, the lower thermodynamic stability of platelet nanoparticles makes their production in preference to substantially spherical metal nanoparticles quite difficult. The present disclosure overcomes this challenge and provides compositions containing significant amounts of platelet nanoparticles.

[0028] As used herein, the term "metal nanoparticles" refers to metal particles having a size of about 150 nm or less in one or more dimensions, particularly about 100 nm or less in one or more dimensions. In substantially spherical metal nanoparticles, the aforementioned values ​​may represent the diameter of the sphere, and in plate-like nanoparticles, the aforementioned values ​​may represent the lateral dimensions or the dimensions (longitudinal thickness) of the metal nanoparticles through the plane. In some cases, the plate-like nanoparticles of the present disclosure may have a lateral dimension of up to about 400 nm, while still being classified as nanoparticles due to having a longitudinal thickness of about 150 nm or less. As used herein, the term "copper nanoparticles" refers to metal nanoparticles made of copper or primarily of copper.

[0029] As used herein, the term "micron-sized metal particles" refers to metal particles that are larger than metal nanoparticles and range in size up to about 1000 μm, such as about 1 μm to about 1000 μm in size, or about 5 μm to about 500 μm in size. The micron-sized metal particles may be substantially spherical in shape or have a non-spherical shape, such as a dendrite or rod shape.

[0030] The term "consolidation" and other variations are used interchangeably herein with the term "fusion" and other variations.

[0031] As used herein, the terms "partially fused", "partially fused" and other derivatives and grammatical equivalents refer to the partial agglomeration of metal nanoparticles with each other. Although fully fused metal nanoparticles may retain little of the structural morphology of the original unfused metal nanoparticles (i.e., they resemble bulk metal with minimal grain boundaries), partially fused metal nanoparticles retain at least some of the structural morphology of the original unfused metal nanoparticles. The properties of partially fused metal nanoparticles can be between the properties of the corresponding bulk metal and the original unfused metal nanoparticles.

[0032] Many scalable methods for mass production of metal nanoparticles within a target size range have been developed, preferably substantially spherical metal nanoparticles within a target size range. Particularly easy metal nanoparticle manufacturing techniques and uses thereof for producing substantially spherical metal nanoparticles are described in, for example, U.S. Patents 7,736,414, 8,105,414, 8,192,866, 8,486,305, 8,834,747, 9,005,483, 9,095,898, 9,700,940, 9,797,032, 9,881,895 and 9,976,042, each of which is incorporated herein by reference in its entirety. This method for producing substantially spherical metal nanoparticles is carried out by reducing a metal precursor (metal salt) in a solution and in the presence of a surfactant system containing one or more surfactants. As further described herein, plate-like nanoparticles can be synthesized by similar methods by varying various reaction conditions. Without being bound by any theory or mechanism, it is believed that the surfactant system can mediate the nucleation and growth of the metal nanoparticles, limit the surface oxidation of the metal nanoparticles, and / or inhibit the metal nanoparticles from extensively aggregating with each other before at least partially fusing together. The metal nanoparticles can then be separated and purified from the reaction mixture by conventional separation techniques, if desired, and processed into a nanoparticle paste.

[0033] Figure 1 and Figure 2 is a diagram of the putative structure of a substantially spherical metal nanoparticle having a surfactant coating thereon. Figure 1 and Figure 2 Circular or spherical metal nanoparticles are shown in FIG, but the concepts shown therein are applicable to plate-like nanoparticles having other geometric shapes. Figure 1 As shown, the metal nanoparticle 10 includes a metal core 12 and a surfactant layer 14 coating the metal core 12. The surfactant layer 14 may contain any combination of surfactants, as described in more detail below. Figure 2 The metal nanoparticles 20 shown are similar to Figure 1The depicted metallic nanoparticles differ in that a metallic core 12 is grown around a core 21, which may be the same or a different metal than the metallic core 12. Because the core 21 is buried deep within the metallic core 12 in the metallic nanoparticle 20, it is not believed to significantly affect the overall nanoparticle properties. Figure 3 is a diagram of the inferred structure of a plate-like nanoparticle 50 having a surfactant layer 54 thereon. Figure 3 52a and 52b, which can be atomically flat in most cases, and a longitudinal face 54 extending between the substantially flat faces 52a and 52b. The substantially flat faces 52a and 52b can be substantially parallel to each other. The surfactant layer 56 covers the substantially flat faces 52a and 52b and the longitudinal face 54. In some cases, different surfactants may be present on the substantially flat faces 52a and 52b and the longitudinal face 54.

[0034] Metal nanoparticles can be single crystal, polycrystalline and / or amorphous. Plate-like nanoparticles and substantially spherical metal nanoparticles, even if co-produced in a given metal nanoparticle synthesis process, can also have different morphologies from each other. For example, plate-like nanoparticles can be single crystal and have no or limited grain boundaries once consolidated, while substantially spherical metal nanoparticles can be amorphous or polycrystalline and exhibit multiple grain boundaries once consolidated. Substantially spherical metal nanoparticles having a size of about 10 nm or less may be significantly more amorphous in nature, due to the energy disadvantages of maintaining a crystalline phase under this size range.

[0035] Without being bound by theory or mechanism, it is believed that the difference in crystallinity is caused by the mechanism of formation and growth of substantially spherical metal nanoparticles and plate-like nanoparticles. Specifically, it is believed that substantially spherical metal nanoparticles grow by Ostwald ripening, while plate-like nanoparticles do not. Ostwald ripening causes consolidation of multiple small particles in substantially spherical metal nanoparticles, resulting in polycrystallinity. The single crystallinity of plate-like nanoparticles can cause their lattices to align during stacking, thereby promoting consolidation and the formation of minimal, low-energy grain boundaries.

[0036] In addition, without being bound by theory or mechanism, it is believed that the growth of plate-like nanoparticles occurs under kinetic growth conditions, while substantially spherical metal nanoparticles can be formed under thermodynamic growth conditions by virtue of their higher thermodynamic stability. Specifically, if the nanoparticle growth can be sufficiently slowed down so that the kinetic growth conditions come into effect, plate-like nanoparticles can be effectively formed. Factors that affect kinetic and thermodynamic growth conditions can include, for example, temperature, growth time, the type and amount of surfactant used, etc.

[0037] It is believed that the dynamics and thermodynamics of metal nanoparticle growth affect how and where surfactants are attached to the growing metal nanoparticles. Amorphous spherical nanoparticles can be initially formed because of their larger thermodynamic stability, thereby avoiding the lone corner (lone corner) or edge atoms required for producing crystalline particles. As nanoparticles begin to grow larger, the crystal structure can become more stable. Once a specific crystal face begins to develop, surfactants with specific geometric structures or shapes can be more preferentially attached to certain crystal faces rather than other crystal faces, thereby further facilitating the formation of crystalline phases. Therefore, if kinetic growth conditions (for example, by controlling temperature, reduction rate and cooling) can be induced by slowing down the nanoparticle formation process, the growth morphology can be changed to facilitate the generation of plate-like nanoparticles with crystalline phases. The selected surfactants and their concentrations can further help the process. Specific surfactants can be preferentially attached to specific crystal faces, and hinder the growth in one direction and facilitate another direction.

[0038] Another advantage of slowing the growth rate according to the foregoing is that higher metal salt concentrations can be used without affecting product quality, including the size and size distribution of the plate-like nanoparticles produced. The increased metal salt concentration can be beneficial for increasing the yield per run. For example, in the case of producing plate-like nanoparticles, a metal salt concentration of about 20% to about 60% higher than in a comparable synthesis that provides substantially spherical metal nanoparticles can be used.

[0039] Suitable metal salts for producing metal nanoparticles may include those that are soluble in the selected organic solvent. Non-limiting examples of suitable metal salts include, but are not limited to, metal halides, metal carboxylates, metal nitrates, and the like. For example, in the disclosure herein, anhydrous copper chloride can be used to form copper nanoparticles, including plate-like nanoparticles.

[0040] Suitable organic solvents for dissolving metal salts and forming metal nanoparticles can include, for example, formamide, N,N-dimethylformamide, dimethyl sulfoxide, dimethyl propylene urea, hexamethylphosphoramide, tetrahydrofuran, glycol dimethyl ether, diglyme, triglyme and tetraglyme. The concentration of metal salt in selected organic solvent can change over a wide range, and is determined by, for example, the solubility properties of the metal salt. Reducing agents suitable for reducing metal salts and promoting the formation of metal nanoparticles can include, for example, alkali metals in the presence of suitable catalysts (for example, naphthalene lithium, naphthalene sodium or naphthalene potassium) or borohydride reducing agents (for example, sodium borohydride, lithium borohydride, potassium borohydride or tetraalkylammonium borohydride).

[0041] The reaction temperature for producing metal nanoparticles (including plate-like nanoparticles) can be in the range of from room temperature (25°C) or even lower, up to about 40°C, or up to about 50°C, or up to about 55°C, or up to about 60°C, or up to about 65°C, or up to about 70°C. The above temperatures represent the maximum temperatures allowed to be reached by the reaction during the formation of metal nanoparticles. The maximum temperature can be adjusted by the addition rate of the reducing agent, as discussed subsequently. The reaction medium can be externally heated while adding the reducing agent and / or heating the reducing agent, provided that the maximum temperature of the reaction remains below the aforementioned value. In some cases, no external heating is applied to the reaction medium for forming plate-like nanoparticles, and the temperature increase in the reaction medium can be caused by the exothermic heat of the reduction of the metal salt by the reducing agent.

[0042] The rate of addition of the reducing agent to the solution containing the metal salt can affect the extent to which the exothermic heating during reduction raises the temperature of the reaction medium. Surprisingly, a suitably slow rate of addition can also further promote the formation of plate-like nanoparticles. In order to help maintain the temperature of the reaction medium below about 50°C, or about 55°C, or about 60°C, or up to about 65°C, or up to about 70°C maximum temperature, the rate of addition of the reducing agent can be maintained at a slow rate to limit the exothermic heating from overheating the reaction mixture and reducing the extent to which the production of plate-like nanoparticles is reduced. In a non-limiting example, the reducing agent can be added to a solution containing a metal salt and a suitable surfactant system such that the reducing agent is completely bound within about 5 minutes or more, or about 6 minutes or more, or about 7 minutes or more, or about 8 minutes or more, or about 9 minutes or more, or about 10 minutes or more, or about 15 minutes or more, or about 20 minutes or more, or about 25 minutes or more, or about 30 minutes or more, or about 40 minutes or more, or about 50 minutes or more, or about 1 hour or more, or about 2 hours or more, and any closed subrange within any of the foregoing values. For example, in non-limiting examples, the reducing agent may be added to the solution containing the metal salt within about 5 minutes to about 30 minutes, or about 10 minutes to about 40 minutes, or about 6 minutes to about 15 minutes, or about 8 minutes to about 20 minutes, or about 10 minutes to about 25 minutes, or about 12 minutes to about 24 minutes, or about 16 minutes to about 32 minutes, or about 18 minutes to about 36 minutes.

[0043] The rate of addition of the reducing agent can be selected to provide a maximum temperature increase of the reaction medium within a desired range. In a non-limiting example, the rate of addition of the reducing agent can be selected to promote a temperature increase of at most about 30°C, or at most about 25°C, or at most about 20°C, or at most about 15°C, or at most about 10°C, or at most about 5°C. As a non-limiting example, the reducing agent can be added to a room temperature solution of the metal salt at a rate sufficient to promote a temperature increase of at most about 20°C or at most about 25°C and a maximum temperature of about 45°C, or the reducing agent can be added to a 30°C solution of the metal salt at a rate sufficient to promote a temperature increase of at most about 10°C and a maximum temperature of about 40°C. In other examples, the reducing agent may be added to a metal salt solution having a temperature of up to about 35° C., about 45° C., or about 55° C. to provide a temperature increase of up to about 5° C., or the reducing agent may be added to a metal salt solution having a temperature of up to about 25° C., about 35° C., or about 45° C. to provide a temperature increase of up to about 10° C. or a temperature increase of up to about 15° C., or the reducing agent may be added to a metal salt solution having a temperature of up to about 20° C., about 30° C., or about 40° C. to provide a temperature increase of up to about 20° C. In other cases, it may be desirable to add the reducing agent to a solution containing a metal salt while maintaining the solution at a temperature below room temperature, such as a temperature in the range of about −10° C. to about 15° C., or about 0° C. to 15° C.

[0044] In other non-limiting examples, the reducing agent can be added to the solution of the metal salt at a rate sufficient to maintain the solution within a temperature range of about 30°C to about 70°C, or about 30°C to about 65°C, or about 30°C to about 60°C, or about 40°C to about 70°C, or about 40°C to about 60°C, or about 50°C to about 70°C, or about 50°C to about 60°C, or about 35°C to about 50°C, or about 35°C to about 60°C, or about 35°C to about 70°C, or about 40°C to about 70°C, or about 40°C to about 60°C, or about 45°C to about 70°C, or about 45°C to about 60°C while forming metal nanoparticles, at least a portion of which comprise plate-shaped nanoparticles, preferably at least about 20% of the metal nanoparticles comprise plate-shaped nanoparticles.

[0045] Once metal nanoparticles are formed when adding a reducing agent, the reaction medium can be kept at this temperature for a period of time or cooled to a lower temperature, such as room temperature, at which nanoparticle separation can occur. In a non-limiting example, the reaction medium can be cooled to room temperature from the heating temperature in about 30 minutes, or in about 1 hour, or in about 2 hours, or in about 3 hours, or in about 4 hours, or in about 6 hours, or in about 10 hours. Slow cooling can also promote the formation of plate-like nanoparticles.

[0046] As described above, the surfactant system present on the surface of the metal nanoparticles may include one or more surfactants. The different properties of various surfactants can be used to customize the properties of the metal nanoparticles. Factors that may be considered when selecting a surfactant or surfactant combination for inclusion on the metal nanoparticles may include, for example, the ease with which the surfactant is emitted from the metal nanoparticles during or before the fusion of the nanoparticles, the nucleation and growth rate of the metal nanoparticles, the metal component of the metal nanoparticles, etc. Forming a surfactant coating on the metal nanoparticles during the synthesis of the metal nanoparticles may desirably limit the ability of the metal nanoparticles to fuse with each other before being heated to a fusion temperature or above, limit the agglomeration of the metal nanoparticles, and promote the formation of a population of metal nanoparticles with a narrower size distribution. The surfactant coating contains at least one surfactant present during the formation of the metal nanoparticles. When more than one type of surfactant is used during the formation of the metal nanoparticles, each type of surfactant or less than each type of surfactant may be located in the surfactant coating. Again, the specific surfactant incorporated into the plate-like nanoparticles as a surfactant coating may depend on the specific surfactants used and their ability to coordinate with the specific faces of the plate-like nanoparticles. When heated above the fusion temperature, the surfactant coating is generally lost during consolidation of the metal nanoparticles, although for lower boiling point surfactants and the strength of their association with the metal nanoparticles, at least some surfactant loss may occur below the fusion temperature. In various embodiments, the surfactant coating can be non-polymeric in nature.

[0047] In some embodiments, an amine surfactant or a combination of amine surfactants (particularly fatty amines) may be present on the metal nanoparticles. For example, an amine surfactant may be particularly desirable for use in combination with copper nanoparticles or metal nanoparticles containing alternative transition metals. In some embodiments, two amine surfactants may be used in combination with each other. In other embodiments, three amine surfactants may be used in combination with each other. In some cases, four amine surfactants may also be used in combination with each other. In a more specific embodiment, when forming metal nanoparticles, primary amines, secondary amines, and diamines may be used in combination with each other. In a more specific embodiment, the three amine surfactants may include long-chain primary amines with straight or branched alkyl groups, secondary amines with straight or branched alkyl groups, and diamines with at least one tertiary alkyl substituent on the nitrogen atom. Therefore, at least some (including one, more than one, or all) of the at least one amine surfactant may contain a branched alkyl chain. Further disclosure about suitable amine surfactants is as follows.

[0048] In some embodiments, the surfactant system may include a primary alkyl amine. In some embodiments, the primary alkyl amine may be C 2 -C18 Alkylamines, wherein the alkyl group may be linear or branched. In some embodiments, the primary alkylamine may be C 6 -C 10 Alkylamine, wherein the alkyl group can be linear or branched. In some embodiments, C 5 -C 6 Primary alkylamines, where the alkyl group can be linear or branched. Without being bound by any theory or mechanism, the exact size of the primary alkylamine can be a balance between being long enough to provide an effective reverse micelle structure during the synthesis of the metal nanoparticles and having easy volatility and / or ease of handling during the consolidation of the nanoparticles. For example, primary alkylamines with more than 18 carbons may also be suitable for use in the present disclosure, but they may be more difficult to handle due to their waxy nature. Specifically, C 6 -C 10 Primary alkyl amines can exhibit a good balance of desirable properties for ease of use.

[0049] Suitable C 2 -C 18 Primary alkylamines can include, for example, n-hexylamine, n-heptylamine, n-octylamine, n-nonylamine or n-decylamine. Although these are all straight-chain primary alkylamines, branched primary alkylamines can also be used in other embodiments. For example, branched primary alkylamines such as 7-methyloctylamine, 2-methyloctylamine or 7-methylnonylamine can be used. In some embodiments, such branched primary alkylamines can be sterically hindered when they are attached to amine nitrogen atoms. The non-limiting examples of such sterically hindered primary alkylamines can include, for example, tert-octylamine, 2-methylpentyl-2-amine, 2-methylhexyl-2-amine, 2-methylheptyl-2-amine, 3-ethyloctyl-3-amine, 3-ethylheptyl-3-amine, 3-ethylhexyl-3-amine, etc. Additional branching can also be present. Without being bound by any theory or mechanism, it is believed that primary alkylamines can serve as ligands in the metal coordination layer, but are easily dissociated therefrom during the consolidation of metal nanoparticles. In some cases, during consolidation, at least a portion of the primary alkylamine can dissipate from the surface of the metal nanoparticles at temperatures below the fusion temperature thereof to form a metal matrix.

[0050] In some embodiments, the surfactant system may include a secondary amine. Secondary amines suitable for forming metal nanoparticles may include a linear, branched, or cyclic C 3 -C 14 , or C 3 -C 8 , or C 4 -C 12 , or C 4 -C 8The two alkyl groups may be the same or different. In some embodiments, branching may occur at the carbon atom bonded to the amine nitrogen atom in one or more alkyl groups, thereby generating significant steric hindrance at the amine nitrogen atom. Suitable secondary amines may include, but are not limited to, dihexylamine, diisobutylamine, di-tert-butylamine, dineopentylamine, di-(2-ethylhexyl)amine, di-tert-amylamine, dicyclopentylamine, dicyclohexylamine, and the like. 4 -C 12 or C 4 -C 8 Secondary amines outside the range of the present invention may be used, but such secondary amines may have undesirable physical properties, such as low boiling points or waxy consistency, which may complicate their handling. In some cases, during consolidation, at least a portion of the secondary alkylamine may dissipate from the surface of the metal nanoparticles below their fusion temperature to form a metal matrix.

[0051] In some embodiments, the surfactant system may include a diamine. In some embodiments, one or both of the nitrogen atoms of the diamine may be substituted with one or two alkyl groups. When two alkyl groups are present on the same nitrogen atom of the diamine, the alkyl groups may be the same or different. Additionally, when both nitrogen atoms are substituted, the same or different alkyl groups may be present. In some embodiments, the alkyl groups in the diamine may be C 1 -C 6 In other embodiments, the alkyl group in the diamine can be C 1 -C 4 Alkyl group or C 3 -C 6 In some embodiments, the C 3 The alkyl group may be straight chain or branched. 3 The or higher alkyl groups may be cyclic. Without being bound by any theory or mechanism, it is believed that the diamines may promote metal nanoparticle formation by promoting nanoparticle nucleation.

[0052] Suitable diamines may include N,N'-dialkylethylenediamines, particularly C 1 -C 4 N,N'-dialkylethylenediamine. The corresponding methylenediamine, propylenediamine, butylenediamine, pentylenediamine or hexylenediamine derivatives can also be used. The alkyl groups in the diamine can be the same or different. The C 1 -C 4Alkyl groups include, for example, methyl, ethyl, propyl and butyl groups, or branched alkyl groups such as isopropyl, isobutyl, sec-butyl and tert-butyl groups. Exemplary N,N'-dialkylethylenediamines suitable for producing metal nanoparticles according to the present disclosure include, for example, N,N'-di-tert-butylethylenediamine, N,N'-diisopropylethylenediamine, and the like.

[0053] In some embodiments, suitable diamines may include N,N,N',N'-tetraalkylethylenediamines, particularly C 1 -C 4 N,N,N',N'-tetraalkylethylenediamine. Corresponding methylenediamine, propylenediamine, butylenediamine, pentylenediamine or hexylenediamine derivatives may also be used. The alkyl groups may also be the same or different and include those described above. Exemplary N,N,N',N'-tetraalkylethylenediamines suitable for forming metal nanoparticles include, for example, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetraethylethylenediamine, and the like.

[0054] In some examples, one or more surfactants (surfactant systems) used to prepare a composition containing plate-like nanoparticles may include at least one amine surfactant, more preferably two or more amine surfactants, and more preferably three or more amine surfactants, such as a combination of primary amines, secondary amines and diamines. One or more or all of the amine surfactants may contain branched alkyl groups. Therefore, in some embodiments, primary amines, secondary amines and diamines can be used in combination with the formation of plate-like nanoparticles, wherein the primary amines, secondary amines and diamines each contain a branched alkyl group. Suitable examples of primary amines, secondary amines and diamines include those listed above. When the surfactant system includes a combination of primary amines, secondary amines and diamines, the ratio of various surfactants relative to each other in the metal salt solution can be adjusted to promote the formation of plate-like nanoparticles. Similarly, the ratio of these surfactants relative to the metal salt can also be adjusted to promote the formation of plate-like nanoparticles, such as by promoting the formation of plate-like nanoparticles under kinetic growth conditions.

[0055] In some examples, the secondary amine can be present in a higher molar amount than the combined amount of the primary amine and the bidentate amine. In some or other examples, the primary amine can be present in a higher molar amount than the bidentate amine. In non-limiting examples, the molar ratio of the primary amine to the bidentate amine can be in the range of about 0.9 to about 3.0, or about 1.0 to about 1.5, or about 1.5 to about 2.0, or about 2.0 to about 2.5, or about 2.5 to about 3.0, or about 1.6 to about 2.2, or about 2.1 to about 2.6, and the molar ratio of the secondary amine to the bidentate amine can be in the range of about 2.5 to about 6.5, or about 2.5 to about 3.0, or about 3.0 to about 3.5, or about 3.5 to about 4.0, or about 4.0 to about 4.5, or about 4.5 to about 4.0, or about 5.0 to about 5.5, or about 5.5 or about 6.0, or about 6.0 to about 6.5, or about 3.1 to about 3.7, or about 3.7 to about 4.3, or about 4.3 to about 4.8. In some or other examples, the molar ratio of the primary amine to the metal salt can be in the range of about 1.5 to about 2.5, or about 1.8 to about 2.3, or about 1.6 to about 2.1, or about 2.1 to about 2.4; the molar ratio of the secondary amine to the metal salt can be in the range of about 4.0 to about 5.2, or about 4.0 to about 4.6, or about 4.6 to about 5.2, or about 4.4 to about 5.0, or about 4.6 to about 4.9; and the molar ratio of the bidentate amine to the metal salt can be in the range of about 0.8 to about 1.6, or about 0.8 to about 1.3, or about 0.9 to about 1.2, or about 1.2 to about 1.6.

[0056] Surfactants other than fatty amines may also be present in the surfactant system. In this regard, suitable surfactants may include, for example, pyridine, aromatic amine, phosphine, mercaptan or any combination thereof. These surfactants may be used in combination with fatty amines (including those mentioned above), or they may be used in surfactant systems in which there is no fatty amine or one or more of aliphatic primary amines, aliphatic secondary amines or bidentate amines are omitted. Further disclosures about suitable pyridine, aromatic amine, phosphine and mercaptan are as follows.

[0057] Suitable aromatic amines may have the formula ArNR 1 R 2 , wherein Ar is a substituted or unsubstituted aryl group, and R 1 and R 2 Same or different. 1 and R 2 Can be independently selected from H or an alkyl or aryl group containing 1 to about 16 carbon atoms. Exemplary aromatic amines suitable for forming metal nanoparticles include, for example, aniline, toluidine, anisidine, N,N-dimethylaniline, N,N-diethylaniline, etc. Other aromatic amines that can be used in combination with metal nanoparticles can be envisioned by those of ordinary skill in the art.

[0058] Suitable pyridines may include pyridine and its derivatives. Exemplary pyridines that can be suitable for promoting the formation of metal nanoparticles include, for example, pyridine, 2-methylpyridine, 2,6-lutidine, collidine, pyridazine, etc. Chelated pyridines may also be used, such as bipyridine chelators. Other pyridines that can be used in conjunction with the formation of metal nanoparticles can be envisioned by those of ordinary skill in the art.

[0059] Suitable phosphines may have the formula PR 3 , wherein R is an alkyl or aryl group containing 1 to about 16 carbon atoms. The alkyl or aryl groups attached to the phosphorus center may be the same or different. Exemplary phosphines that may be present when forming metal nanoparticles include, for example, trimethylphosphine, triethylphosphine, tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, triphenylphosphine, etc. Phosphine oxides may also be used in a similar manner. In some embodiments, surfactants comprising two or more phosphine groups configured to form a chelate ring may also be used. Exemplary chelated phosphines may include 1,2-bisphosphines, 1,3-bisphosphines and bisphosphines, such as BINAP. Other phosphines that may be used in conjunction with forming metal nanoparticles may also be conceived by a technician of ordinary skill in the art.

[0060] Suitable thiols may have the formula RSH, wherein R is an alkyl or aryl group having about 4 to about 16 carbon atoms. Exemplary thiols that may be used in conjunction with forming metal nanoparticles include, for example, butanethiol, 2-methyl-2-propanethiol, hexanethiol, octanethiol, thiophenol, and the like. In some embodiments, surfactants comprising two or more thiol groups configured to form a chelate ring may also be used. Exemplary chelated thiols may include, for example, 1,2-dithiols (e.g., 1,2-ethanethiol) and 1,3-dithiols (e.g., 1,3-propanethiol). Other thiols that may be used in conjunction with forming metal nanoparticles may be envisioned by those of ordinary skill in the art.

[0061] Copper can be a particularly ideal metal for incorporation into metal nanoparticles due to its low cost, strength, and excellent electrical and thermal conductivity values, as well as other advantages further described herein. Aliphatic amine surfactants (including those described above) can also easily form metal-ligand bonds with copper and promote the formation of copper nanoparticles. Although copper nanoparticles can be advantageous for the above reasons, it should be understood that in some cases, other types of metal nanoparticles can be used. Other metal nanoparticles that can be formed according to the disclosure herein include, for example, aluminum nanoparticles, palladium nanoparticles, silver nanoparticles, gold nanoparticles, iron nanoparticles, cobalt nanoparticles, nickel nanoparticles, titanium nanoparticles, zirconium nanoparticles, hafnium nanoparticles, tantalum nanoparticles, and the like. In the disclosure herein, any of the aforementioned metal nanoparticles may contain plate-like nanoparticles, preferably in an amount exceeding 20%, based on the total nanoparticles. Micron-sized particles of these metals may also be present in nanoparticle pastes containing metal nanoparticles, which may provide processing advantages in some cases.

[0062] Suitable copper alloys can be formed in situ by co-reduction / precipitation during the initial process of forming metal nanoparticles. In one configuration, additional metal salts can be co-reduced with the copper salt. In another configuration, decomposed metal organic compounds can be present during reduction to form copper nanoparticles. In another process configuration, the compound can be reduced or decomposed before forming copper nanoparticles in the same reaction vessel. In this configuration, nanoparticle nucleation seeds can be generated to promote the growth of metal nanoparticles around the core. At least a portion of the metal nanoparticles prepared according to any of the foregoing can be plate-like nanoparticles.

[0063] Thus, the present disclosure provides a composition comprising a plurality of metal nanoparticles having a surfactant coating thereon, wherein at least a portion of the metal nanoparticles are plate-shaped nanoparticles, and the surfactant coating comprises at least one surfactant. More specifically, the composition may comprise a plurality of metal nanoparticles having a surfactant coating thereon, wherein at least 20% of the metal nanoparticles are plate-shaped nanoparticles, and the surfactant coating comprises at least one surfactant. In various cases, the metal nanoparticles may comprise copper nanoparticles or consist essentially of copper nanoparticles. In some embodiments, the plate-shaped nanoparticles may comprise at least a majority of the metal nanoparticles.

[0064] The plate-like nanoparticles may account for about 20% to about 100% of the metal nanoparticles in the composition by volume. For example, the plate-like nanoparticles may include about 20% or more, or about 30% or more, or about 40% or more, or about 50% or more, or about 60% or more, or about 70% or more, or about 80% or more, or about 90% or more, or about 95% or more of the plurality of metal nanoparticles.

[0065] In addition to plate-like nanoparticles, a plurality of metal nanoparticles may also include a plurality of substantially spherical metal nanoparticles. When present, substantially spherical metal nanoparticles may have a diameter of about 150nm or less, or about 70nm or less, or about 20nm or less, or about 10nm or less, such as about 5nm to about 20nm, or about 10nm to about 30nm, or about 20nm to about 50nm, or about 50nm to about 70nm, or any combination thereof. When present, substantially spherical metal nanoparticles may account for about 80% to about 10% of the plurality of metal nanoparticles by volume. For example, substantially spherical metal nanoparticles may include about 20% or less, or about 30% or less, or about 40% or less, or about 50% or less, or about 60% or less, or about 70% or less, or about 80% or less of the plurality of metal nanoparticles. In some embodiments, a plurality of substantially spherical metal nanoparticles with bimodal particle size distribution may be present in combination with the plate-like nanoparticles of the present disclosure.

[0066] Substantially spherical metal nanoparticles may have a circularity of about 0.8 or greater, such as about 0.8 to about 1, or about 0.80 to about 0.95, or about 0.90 to about 1.0, or about 0.93 to about 0.99, or about 0.95 to about 0.99, or about 0.97 to about 0.99, or about 0.98 to about 1.0. To determine the circularity of a given particle, the perimeter (P) and area (A) of the particle can be evaluated from the optical image. The relationship C can then be used to determine the circularity of the particle. EA / P determines the roundness, where C EA It is the circumference of the circle whose area is equal to the area (A) of the actual particle.Therefore, roundness represents the ratio of the circumference of nanoparticles compared with the circumference of a perfect sphere with the same radius.On the contrary, plate-like nanoparticles can have 0.8 or less, such as 0.5 or less, or about 0.4 or less, or about 0.3 or less, or about 0.2 or less roundness, provided that the plate-like nanoparticles are not substantially circular (disc-like).Disc-like plate-like nanoparticles can have a roundness similar to substantially spherical metal nanoparticles.

[0067] In non-limiting examples, the plate-like nanoparticles described herein may have a longitudinal thickness (i.e., through the plane of the plate, thus representing a through-plane thickness) ranging from about 5 nm to about 40 nm, or about 5 nm to about 10 nm, or about 5 nm to about 20 nm, or about 10 nm to about 20 nm, or about 15 nm to about 30 nm, or about 20 nm to about 40 nm.

[0068] In non-limiting examples, the plate-like nanoparticles described herein may have a maximum dimension (any dimension, including through the plane of the plate) ranging from about 10 nm to about 400 nm, or about 10 nm to about 100 nm, or about 50 nm to about 200 nm, or about 10 nm to about 50 nm, or about 100 nm to about 200 nm, or about 200 nm to about 400 nm.

[0069] In non-limiting examples, the plate-shaped nanoparticles described herein may have a face aspect ratio (the ratio of the length to the width of a face of the plate, excluding the through-plane thickness of the plate) ranging from about 1.5 to about 30, or about 1.5 to about 3, or about 2 to about 4, or about 3 to about 5, or about 5 to about 8, or about 8 to about 12, or about 10 to about 15, or about 12 to about 20, or about 15 to about 25, or about 15 to about 30, or about 20 to about 25, or about 25 to about 30.

[0070] In non-limiting examples, the plate-shaped nanoparticles described herein may have a longitudinal aspect ratio (ratio of length or width to longitudinal or through-plane thickness) ranging from about 1.5 to about 100, or about 1.5 to about 3, or about 2 to about 5, or about 3 to about 10, or about 5 to about 8, or about 8 to about 12, or about 10 to about 15, or about 12 to about 20, or about 15 to about 25, or about 15 to about 30, or about 20 to about 25, or about 25 to about 30, or about 20 to about 50, or about 30 to about 75, or about 35 to about 100.

[0071] In addition to the above dimensions, the shape of the plate-like nanoparticles is not considered to be particularly limited. In non-limiting examples, the plate-like nanoparticles can have shapes such as triangles, rectangles, squares, disks (including oval and circular disks), pentagons, hexagons, etc. or any combination thereof.

[0072] For non-ovate or circular plate-like nanoparticles (i.e., polygonal plate-like nanoparticles), the size range of the length of each edge can be about 5nm to about 400nm, or about 5nm to about 300nm, or about 5nm to about 200nm, or about 10nm to about 200nm, or about 5nm to about 50nm, or about 5nm to about 25nm, or about 50nm to about 100nm. In a non-limiting example, a triangular plate-like nanoparticle may have an edge with a size range of about 5nm to about 200nm, and a hexagonal plate-like nanoparticle may have an edge with a size range of about 5nm to about 150nm. The above values ​​represent edge lengths, rather than the maximum size (edge-to-center distance) of the plate-like nanoparticles. The length of each edge in the plate-like nanoparticles can be the same or different. Therefore, the shape of the polygonal plate-like nanoparticles can be regular or irregular. In some cases, the top of the polygonal plate-like nanoparticle can be round.

[0073] The composition containing plate-like nanoparticles described above can be further incorporated into various nanoparticle preparations, which can facilitate the distribution of plate-like nanoparticles and their consolidation. Suitable preparations may include nanoparticle pastes, sprayable preparations, inks, etc. Exemplary disclosures involving such nanoparticle pastes and similar preparations are as follows. Likewise, copper nanoparticles (e.g., copper nanoparticles having a plate-like morphology, optionally combined with substantially spherical copper nanoparticles) represent only one type of metal nanoparticle that can be appropriately incorporated into a nanoparticle paste and further consolidated according to the disclosure herein.

[0074] Nanoparticle pastes can be prepared by dispersing the generated or separated metal nanoparticles in an organic matrix containing one or more organic solvents and various other optional components. As used herein, the terms "nanoparticle paste preparation" and "nanoparticle paste" are used interchangeably and synonymously refer to a fluid composition containing dispersed metal nanoparticles that is suitable for distribution using the desired technology. Suitable pastes may include fluid dispersions that cannot flow freely due to their viscosity, while fluid dispersions including inks can flow freely. The use of the term "paste" does not necessarily mean only the adhesive function of the paste. The distribution of metal nanoparticles at desired locations can be promoted by judiciously selecting organic solvents and other additives in the nanoparticle paste, the loading of metal nanoparticles, etc.

[0075] During consolidation of metal nanoparticles, cracking and shrinkage sometimes occur, especially when substantially spherical metal nanoparticles are used. In contrast, plate-like nanoparticles overlap each other more effectively than substantially spherical metal nanoparticles, making it more difficult for cracks to be generated and propagated. Figure 4 is a diagram showing substantially spherical metallic nanoparticles 301 in a close-packed configuration 300. As shown, even the close-packed configuration 300 provides a route for crack propagation 302 through the consolidated grain boundaries 304 after they are formed. Figure 5 400 is a diagram showing plate-like nanoparticles 401 in an overlapping, stacked, deposited configuration 400. As shown, in the case of the stacked plate-like nanoparticles 401, there is no continuous path through which crack progression 402 can easily proceed.

[0076] One way in which a nanoparticle paste containing plate-like nanoparticles can further promote the reduction of the degree of cracking and void formation after the consolidation of metal nanoparticles is by maintaining a high solid content. Therefore, the nanoparticle paste disclosed herein may contain at least about 30% by weight of metal nanoparticles, specifically about 30% to about 98% of metal nanoparticles by weight of the nanoparticle paste, or about 50% to about 98% of metal nanoparticles by weight of the nanoparticle paste, or about 70% to about 98% of metal nanoparticles by weight of the nanoparticle paste. In addition, in some embodiments, in addition to metal nanoparticles, a small amount (e.g., about 0.01% to about 15%, or about 35% or about 70%, or about 10% or about 35% by weight of the paste composition) of micron-sized metal particles may also be present. Such micron-sized metal particles can advantageously promote the fusion of metal nanoparticles into a bulk metal matrix and further reduce the incidence of cracking, shrinkage and total porosity. For example, compared to the shrinkage of about 20-40 volume % when there are no micron-sized particles, when there are micron-sized particles, the shrinkage when forming fused copper nanoparticles can be reduced to about 5 volume % or lower. When plate-like nanoparticles are present in nanoparticle pastes and similar preparations, even when there are no micron-sized metal particles, reduced shrinkage can be achieved, thereby allowing micron-sized metal nanoparticles to be used in a lower amount or not at all in the nanoparticle paste disclosed herein. Reduced shrinkage may be due to the plate-like nanoparticles being closer together due to improved stacking from the beginning. Micron-sized metal particles (when present) are not liquefied and undergo direct consolidation, but can be simply connected together after contacting metal nanoparticles that have been raised to above their fusion temperature. In addition, plate-like nanoparticles can provide better contact between two or more micron-sized metal particles (in some cases further assisted by the flexibility of the plate-like nanoparticles), thereby bridging the micron-sized metal particles together once the fusion temperature is raised above. These factors can reduce the porosity generated after the plate-like nanoparticles and micron-sized metal particles are fused together. Micron-sized metal particles can contain metals identical or different from metal nanoparticles. For example, micron-sized copper particles can be used in combination with copper nanoparticles containing at least some plate-like nanoparticles. Suitable metals for micron-sized metal particles can include, for example, copper, silver, gold, aluminum, tin, etc. Micron-sized graphite particles can also be included as another type of micron-sized particles. Carbon nanotubes and / or graphene can also be included as another type of micron-sized particles. Carbon black and / or nano-carbon can be included in other cases. For example, other additives can also be included, such as diamond particles, AlN and cubic BN (boron nitride). The suitable form of other additives can include, for example, a length of about 50 microns to about 350 microns and a diameter of about 5 microns to about 25 microns of grinding fibers.

[0077] Solvents that form organic matrices present in nanoparticle pastes or similar formulations can also be used to promote the reduction of cracking and void formation during the consolidation of metal nanoparticles by judiciously selecting. Customized combinations of organic solvents can desirably reduce the incidence of cracking and void formation. More particularly, organic matrices containing one or more hydrocarbons (saturated, monounsaturated, polyunsaturated (2 or more double bonds) or aromatic), one or more alcohols, one or more amines, and optionally one or more organic acids can be particularly effective for this purpose. In some embodiments, in addition to or as a substitute for other solvent components of the nanoparticle paste, one or more esters, ethers, ketones, aldehydes, and / or one or more anhydrides may be included. Without being bound by any theory or mechanism, it is believed that the organic solvent of this combination can promote the removal and isolation of surfactant molecules around metal nanoparticles during consolidation, so that metal nanoparticles can more easily fuse together. More specifically, it is believed that hydrocarbon and alcohol solvents can passively dissolve surfactant molecules released from metal nanoparticles by Brownian motion and reduce their ability to reattach thereto. Consistent with the passive dissolution of surfactant molecules, amine and organic acid solvents are able to actively sequester surfactant molecules through chemical interactions, making them no longer available for recombination with metal nanoparticles.

[0078] The solvent composition can be further tailored to reduce the suddenness of the volume shrinkage that occurs during surfactant removal and metal nanoparticle consolidation. Specifically, more than one member of each class of organic solvents (i.e., hydrocarbons, alcohols, amines, and optional organic acids) can be present in the organic matrix, wherein the members of each class have boiling points that are separated from each other by a set degree. For example, in some embodiments, the various members of each class can have boiling points that are separated from each other by about 20°C to about 50°C. By using such a solvent mixture, sudden volume changes caused by rapid loss of solvent can be minimized during metal nanoparticle consolidation because the various components of the solvent mixture can be gradually removed over a wide range of boiling points (e.g., about 50°C to about 250°C).

[0079] In some embodiments, at least some of the one or more organic solvents may have a boiling point of about 100°C or higher. In some embodiments, at least some of the one or more organic solvents may have a boiling point of about 200°C or higher or about 300°C or higher. In some embodiments, one or more organic solvents may have a boiling point range between about 50°C and about 350°C, or between about 50°C and about 200°C, or between about 100°C and about 200°C, or between about 150°C and about 350°C. The use of high boiling point organic solvents can desirably increase the pot life of the nanoparticle paste and limit the rapid loss of solvent, which can cause cracking and void formation during nanoparticle consolidation. In some embodiments, at least one organic solvent can have a boiling point higher than one or more boiling points of one or more surfactants associated with the metal nanoparticles. Therefore, the surfactant can be removed from the metal nanoparticles by evaporation before removing the organic solvent, and in some examples, at least a portion of the surfactant can be removed below the fusion temperature of the metal nanoparticles.

[0080] In some embodiments, the organic matrix may include one or more alcohols. In various embodiments, the alcohol may include monohydric alcohols, dihydric alcohols, trihydric alcohols, glycol ethers (e.g., diethylene glycol and triethylene glycol), alkanolamines (e.g., ethanolamine, triethanolamine, etc.), or any combination thereof. In some embodiments, one or more hydrocarbons can exist in combination with one or more alcohols. As described above, it is believed that alcohol and hydrocarbon solvents can passively promote the dissolution of surfactants because they are removed from metal nanoparticles by Brownian motion and limit their reassociation with metal nanoparticles. In addition, hydrocarbon and alcohol solvents are only weakly coordinated with nanoparticles, so they cannot simply replace the displaced surfactants in the coordination layer of nanoparticles. Exemplary but non-limiting examples of alcohol and hydrocarbon solvents that can exist include, for example, light aromatic petroleum distillates (CAS 64742-95-6), hydrotreated light petroleum distillates (CAS 64742-47-8), tripropylene glycol methyl ether, light petroleum (CAS 68551-17-7, C 10 -C 13 In some embodiments, polyketone solvents can be used in a similar manner.

[0081] In some embodiments, the organic matrix can contain one or more amines and optionally one or more organic acids. In some embodiments, one or more amines and one or more organic acids can be present in an organic matrix that also includes one or more hydrocarbons and one or more alcohols. As described above, it is believed that amines and organic acids can actively isolate surfactants that have been passively dissolved by hydrocarbon and alcohol solvents, thereby making the surfactants unavailable for re-association with metal nanoparticles. Therefore, organic solvents containing a combination of one or more hydrocarbons, one or more alcohols, one or more amines and one or more organic acids can provide synergistic benefits for promoting consolidation of metal nanoparticles. Illustrative but non-limiting examples of amine solvents that can be present include, for example, tallow amine (CAS 61790-33-8), alkyl (C 8 -C 18 ) unsaturated amine (CAS 68037-94-5), di(hydrogenated tallow) amine (CAS 61789-79-5), dialkyl (C 8 -C 20 )amine (CAS 68526-63-6), alkyl (C 10 -C 16 ) dimethylamine (CAS67700-98-5), alkyl (C 14 -C 18 ) dimethylamine (CAS 68037-93-4), dihydrogenated tallow methylamine (CAS 61788-63-4) and trialkyl (C 6 -C 12 ) amine (CAS 68038-01-7). Illustrative but non-limiting examples of organic acid solvents that can be present in the nanoparticle paste include, for example, caprylic acid, nonanoic acid, capric acid, undecanoic acid, lauric acid, tridecanoic acid, myristic acid, pentadecanoic acid, palmitic acid, heptadecanoic acid, stearic acid, nonadecanoic acid, α-linolenic acid, octadecatenic acid, oleic acid, and linoleic acid.

[0082] In some embodiments, the organic matrix can include more than one hydrocarbon, more than one alcohol, more than one amine and more than one optional organic acid. For example, in some embodiments, each class of organic solvents can have two or more members, or three or more members, or four or more members, or five or more members, or six or more members, or seven or more members, or eight or more members, or nine or more members, or ten or more members. In addition, the number of members in each class of organic solvents can be the same or different. The specific benefits of using multiple members of each class of organic solvents are described hereinafter.

[0083] A particular advantage of using multiple members in each class of organic solvents may include the ability to provide a wider range of boiling points in the nanoparticle paste. By providing a wider range of boiling points, the organic solvent can be gradually removed as the temperature rises, while affecting the consolidation of the metal nanoparticles, thereby limiting volume shrinkage and not conducive to cracking. As a result, better structural integrity of the connection can be achieved. By gradually removing the organic solvent in this way, less temperature control may be required to promote the slow removal of the solvent compared to if a single solvent with a narrower boiling point range is used. In some embodiments, the members of each class of organic solvents may have a boiling point range between about 50°C and about 200°C, or between about 50°C and about 250°C, or between about 100°C and about 200°C, or between about 100°C and about 250°C. In some cases, boiling points up to about 350°C may be suitable. In a more particular embodiment, the various members of each class of organic solvents can each have boiling points separated from each other by at least about 20°C, particularly about 20°C to about 50°C. More specifically, in some embodiments, each hydrocarbon can have a boiling point that differs from other hydrocarbons in the organic matrix by about 20°C to about 50°C, each alcohol can have a boiling point that differs from other alcohols in the organic matrix by about 20°C to about 50°C, each amine can have a boiling point that differs from other amines in the organic matrix by about 20°C to about 50°C, and each optional organic acid can have a boiling point that differs from other organic acids in the organic matrix by about 20°C to about 50°C. The more members of each class of organic solvents there are, the smaller the difference between the boiling points becomes. By having a smaller boiling point difference, the solvent removal can be made more continuous, thereby limiting the degree of volume shrinkage that occurs at each stage. When there are four to five or more members in each class of organic solvents (e.g., four or more hydrocarbons, four or more alcohols, four or more amines, and four or more organic acids; or five or more hydrocarbons, five or more alcohols, five or more amines, and five or more organic acids), each occupant has a boiling point separated from each other within the above range.

[0084] In addition to the metal nanoparticles and organic solvents, other additives may also be present in the nanoparticle paste, including micron-sized metal particles or other micron-sized particles described above. Such additional additives can include, for example, rheology control aids, thickeners, micron-sized conductive additives, nano-sized conductive additives, and any combination thereof. Chemical additives can also be present. As discussed below, it may be particularly advantageous to include micron-sized conductive additives (such as micron-sized metal particles). In some cases, it may be desirable to include nano-sized or micron-sized diamond or other thermally conductive additives.

[0085] In some embodiments, the nanoparticle paste can contain about 0.01% to about 15% by weight of micron-sized metal particles, or about 1% to about 10% by weight of micron-sized metal particles, or about 1% to about 5% by weight of micron-sized metal particles, or about 0.1% to about 35% by weight of micron-sized particles, or about 10% to about 35% by weight of micron-sized particles, or about 35% to about 70% by weight of micron-sized metal particles. The inclusion of micron-sized metal particles in the nanoparticle paste can desirably reduce the incidence of cracking due to shrinkage during consolidation of the metal nanoparticles. In addition, the use of plate-shaped nanoparticles can reduce the incidence of shrinkage and cracking compared to substantially spherical metal nanoparticles, even when the micron-sized metal particles are omitted or used in lower amounts. Without being bound by any theory or mechanism, it is believed that when the metal nanoparticles liquefy and form a transient liquid coating on the micron-sized metal particles and fill the voids therebetween, the micron-sized metal particles can partially consolidate with each other. In essence, metal nanoparticles play the role of "glue" that combines micron-sized particles together. In some embodiments, the size of micron-sized metal particles in at least one dimension can be between about 500nm and about 100 microns, or the size in at least one dimension can be about 500nm to about 10 microns, or the size in at least one dimension can be about 100nm to about 5 microns, or the size in at least one dimension can be about 100nm to about 10 microns, or the size in at least one dimension can be about 100nm to about 1 micron, or the size in at least one dimension can be about 100nm to about 1 micron, or the size in at least one dimension can be about 1 micron to about 10 microns, or the size in at least one dimension can be about 5 microns to about 10 microns, or the size in at least one dimension can be about 1 micron to about 100 microns. Micron-sized metal particles can contain the same metal as metal nanoparticles or contain different metals. Therefore, metal alloys can be manufactured by including micron-sized metal particles different from the metal of metal nanoparticles in nanoparticle pastes. Suitable micron-sized metal particles can include, for example, Cu, Ni, Al, Fe, Co, Mo, Ag, Zn, Sn, Au, Pd, Pt, Ru, Mn, Cr, Ti, V, Mg or Ca particles. Borides, carbides, phosphides, nitrides and silicides of these metals, and combinations thereof, can also be used. Non-metallic particles, such as, for example, Si and B micron-sized particles, including borides, carbides, phosphides, nitrides and silicides thereof, can be used in a similar manner. Specific examples of particles that may be present in the nanoparticle paste include SiC, AlN, SiN, BN, etc. In some embodiments, the micron-sized metal particles may be in the form of metal flakes, such as high aspect ratio copper flakes. That is, in some embodiments, the nanoparticle paste described herein may include a mixture of copper nanoparticles and high aspect ratio copper flakes.Specifically, in some embodiments, the nanoparticle paste may include about 30% to about 98% copper nanoparticles by weight and about 0.01% to about 15% high aspect ratio copper flakes by weight, or about 0.1% to about 35% high aspect ratio copper flakes by weight, or about 1% to about 35% high aspect ratio copper flakes by weight, or about 35% to about 70% high aspect ratio copper flakes by weight.

[0086] Other micron-sized metal particles that can be used equivalent to high aspect ratio metal flakes include, for example, metal nanowires and other high aspect ratio particles, which can be up to about 300 microns or about 500 microns in length. According to various embodiments, the ratio of metal nanoparticles to metal nanowires can be in the range of about 10:1 to about 40:1. For example, suitable nanowires can have a length between about 5 microns to about 50 microns or about 100 microns and a diameter between about 100nm to about 200nm. Grinding fibers (e.g., carbon fibers, ceramic fibers, metal fibers, and similar fibers with high thermal conductivity) can be used similarly. In a non-limiting example, suitable grinding fibers can have a diameter of about 5 microns to about 25 microns and a length of about 50 microns to about 500 microns.

[0087] In some embodiments, nano-scale conductive additives can also be present in the nanoparticle paste. These additives can desirably provide further structural reinforcement and reduce shrinkage during consolidation of the metal nanoparticles. In addition, the inclusion of nano-scale conductive additives can increase electrical and thermal conductivity values, which can approach or even exceed the electrical and thermal conductivity values ​​of the corresponding bulk metal after nanoparticle consolidation. In some embodiments, the size range of the nano-scale conductive additives can be between about 1 micron and about 100 microns, or between about 1 micron and about 300 microns in at least one dimension. Suitable nano-scale conductive additives can include, for example, carbon nanotubes, graphene, etc. Nano-scale sized carbon fibers can be used similarly. When present, the nano-particle paste can contain nano-scale conductive additives of about 1% to about 15% by weight, or nano-scale conductive additives of about 1% to about 10% by weight, or nano-scale conductive additives of about 1% to about 5% by weight.

[0088] Additional substances that can also optionally be present include, for example, flame retardants, UV protectants, antioxidants, carbon black, graphite, fiber materials (eg, chopped carbon fiber materials), diamond, and the like.

[0089] In addition to nanoparticle pastes, the metal nanoparticles disclosed herein can be incorporated into sprayable formulations and inks, which can be distributed by alternative procedures such as inkjet printing, stencil printing, gravure printing, aerosol spraying, painting, dipping, 3-D printing, etc. Sprayable formulations and inks can similarly contain metal nanoparticles dispersed in a suitable solvent, but have a lower viscosity than the above-mentioned nanoparticle paste. Suitable sprayable formulations can have a viscosity of about 1 cP to about 500 cP or about 1 cP to about 100 cP, and contain a load of metal nanoparticles, wherein at least about 20% are plate-like nanoparticles, ranging from about 1 wt % to about 35 wt %, or about 10 wt % to about 25 wt %, or about 1 wt % to about 10 wt %, or about 10 wt % to about 15 wt %. Sprayable formulations and inks containing metal nanoparticles can include one or more organic solvents and optional water, in which the metal nanoparticles can be dispersed before being distributed on the substrate. When desired, additional additives can also be present in the sprayable formulations and inks. As non-limiting examples, sprayable formulations may be dispensed using an aerosol propellant, forced pressurization, suction, or a mechanical pump.

[0090] The method of consolidating metal nanoparticles including plate-like nanoparticles may include depositing the metal nanoparticles on a substrate and consolidating the metal nanoparticles to form a bulk metal matrix on the substrate. Suitable substrates are not particularly limited. In various embodiments, consolidating the metal nanoparticles may include heating the metal nanoparticles at or above the fusion temperature of the metal nanoparticles. Removal of solvent from the metal nanoparticles may occur during consolidation, which may further promote the formation of a bulk metal matrix. Figure 6 The stacking of plate-like nanoparticles is shown.

[0091] Figure 6 is a diagram showing how plate-like nanoparticles can undergo stacking and consolidation with each other. Figure 6 As shown, the plate-like nanoparticles 500 may initially be randomly distributed in the solvent of the nanoparticle paste 502. As the solvent gradually dissipates from the substrate surface, the plate-like nanoparticles 500 may be organized into a stacked structure 510, wherein the plate-like nanoparticles 500 are stacked on top of each other in an overlapping or non-overlapping manner. After consolidating the plate-like nanoparticles 500 at or above the fusion temperature, a bulk metal matrix 520 may be produced.

[0092] Embodiments disclosed herein include:

[0093] A. Plate-like nanoparticle composition. The composition comprises: a plurality of metal nanoparticles having a surfactant coating thereon, at least a portion of the metal nanoparticles are plate-like nanoparticles, and the surfactant coating comprises at least one surfactant.

[0094] A1. A nanoparticle paste comprising the composition of A.

[0095] A2. A sprayable formulation comprising the composition of A.

[0096] A3. An ink comprising the composition of A.

[0097] B. A method of forming a bulk metal. The method comprises: depositing the metal nanoparticles of A on a substrate, and consolidating the metal nanoparticles to form a bulk metal matrix.

[0098] C. A method for forming plate-like nanoparticles. The method comprises: providing a solution comprising a metal salt and at least one surfactant dissolved in an organic solvent; and adding a reducing agent to the solution at a rate sufficient to form a plurality of metal nanoparticles, wherein at least a portion of the metal nanoparticles are plate-like nanoparticles having a surfactant coating thereon comprising at least one surfactant; wherein the reducing agent is added at a rate sufficient to maintain the solution at a temperature of about 60° C. or less while forming the metal nanoparticles.

[0099] Embodiments A to C may have one or more of the following additional elements in any combination:

[0100] Element 1: wherein the plate-like nanoparticles have a thickness ranging from about 5 nm to about 40 nm.

[0101] Element 2: wherein the plate-like nanoparticles have a longitudinal aspect ratio ranging from about 1 to about 100.

[0102] Element 3: wherein the plate-like nanoparticles have a maximum dimension ranging from about 10 nm to about 400 nm.

[0103] Element 4: wherein the plurality of metal nanoparticles further comprises a plurality of substantially spherical metal nanoparticles.

[0104] Element 5: wherein the metal nanoparticles comprise copper nanoparticles.

[0105] Element 6: wherein the at least one surfactant comprises at least one amine surfactant.

[0106] Element 7: wherein the at least one amine surfactant comprises two or more amine surfactants, at least one of the two or more amine surfactants is an N,N'-dialkylethylenediamine.

[0107] Element 8: In which the plate-like nanoparticles are atomically flat.

[0108] Element 9: wherein consolidating the metal nanoparticles comprises heating the nanoparticle paste to above a fusion temperature of the metal nanoparticles.

[0109] Element 10: wherein the reducing agent is added to the solution over a period of about 10 minutes or more.

[0110] Element 11: wherein when the reducing agent is added, the temperature of the solution increases by about 10°C to about 15°C.

[0111] Element 12: wherein the reducing agent is added at a rate sufficient to maintain the solution at a temperature of about 40°C to about 60°C while forming the metal nanoparticles.

[0112] As non-limiting examples, exemplary combinations suitable for A through C include, but are not limited to: 1, 2 and / or 3 and 4; 1, 2 and / or 3 and 5; 1, 2 and / or 3 and 6; 1, 2 and / or 3 and 7; 1, 2 and / or 3 and 8; 1 and 2; 1 and 3; 1 and 4; 1 and 5; 1 and 6; 1 and 7; 1 and 8; 2 and 3; 2 and 4; 2 and 5; 2 and 6; 2 and 7; 2 and 8; 3 and 4; 3 and 5; 3 and 6; 3 and 7; 3 and 8; 4 and 5; 4 and 6; 4 and 7; 4 and 8; 5 and 6; 5 and 7; 5 and 8; 6 and 7; 6 and 8; and 7 and 8. Any of the foregoing combinations may be further combined with one or more of 9, 10, 11, and / or 12. Additional exemplary combinations suitable for C include, but are not limited to: 10 and 11; 10 and 12; 11 and 12; and 10 through 12.

[0113] Additional embodiments disclosed herein include:

[0114] Embodiment 1. A composition comprising: a plurality of metal nanoparticles having a surfactant coating thereon, at least about 20% of the metal nanoparticles are plate-like nanoparticles, and the surfactant coating comprises at least one surfactant.

[0115] Embodiment 2. The composition of embodiment 1, wherein at least a majority of the metal nanoparticles are plate-like nanoparticles.

[0116] Embodiment 3. The composition of Embodiment 1, or the composition of Embodiment 1 or Embodiment 2, wherein at least about 80% of the metal nanoparticles are plate-like nanoparticles.

[0117] Embodiment 4. The composition of Embodiment 1, or the composition of any one of Embodiments 1-3, wherein the plate-like nanoparticles have a longitudinal thickness ranging from about 5 nm to about 40 nm.

[0118] Embodiment 5. The composition of Embodiment 1, or the composition of any one of Embodiments 1-4, wherein the plate-like nanoparticles have a longitudinal aspect ratio ranging from about 1 to about 100.

[0119] Embodiment 6. The composition of Embodiment 1, or the composition of any one of Embodiments 1-5, wherein the plate-like nanoparticles have a maximum dimension ranging from about 10 nm to about 400 nm.

[0120] Embodiment 7. The composition of any one of Embodiments 1-6, wherein the plurality of metal nanoparticles further comprises a plurality of substantially spherical metal nanoparticles.

[0121] Embodiment 8. The composition of any one of Embodiments 1-6, or the composition of any one of Embodiments 1-7, wherein the metal nanoparticles comprise copper nanoparticles.

[0122] Embodiment 9. The composition of any one of Embodiments 1-6, or the composition of any one of Embodiments 1-8, wherein the at least one surfactant comprises at least one amine surfactant.

[0123] Embodiment 10. The composition of embodiment 9, wherein the at least one amine surfactant comprises two or more amine surfactants.

[0124] Embodiment 11. The composition of Embodiment 9, or the composition of Embodiment 9 or Embodiment 10, wherein the at least one amine surfactant comprises one or more branched chain amines.

[0125] Embodiment 12. The composition of any one of Embodiments 1-6, or the composition of any one of Embodiments 1-11, wherein the plate-like nanoparticles have a fusion temperature ranging from about 180°C to about 240°C.

[0126] Embodiment 13. A nanoparticle paste comprising the composition of any one of Embodiments 1-6, or the composition of any one of Embodiments 1-12.

[0127] Embodiment 14. A sprayable formulation comprising the composition of any one of embodiments 1-6, or the composition of any one of embodiments 1-12.

[0128] Embodiment 15. An ink comprising the composition according to any one of embodiments 1-6, or the composition according to any one of embodiments 1-12.

[0129] Embodiment 16. A method comprising: depositing a composition according to any one of Embodiments 1-6 or a composition according to any one of Embodiments 1-13 on a substrate; and consolidating the metal nanoparticles to form a bulk metal matrix on the substrate.

[0130] Embodiment 17. The method of Embodiment 16, wherein consolidating the metal nanoparticles comprises heating the composition to above a fusion temperature of the metal nanoparticles.

[0131] Embodiment 18. The method of embodiment 16, or the method of embodiment 16 or embodiment 17, wherein the plate-like nanoparticles have a fusion temperature ranging from about 180°C to about 240°C.

[0132] Embodiment 19. The method of Embodiment 16, or the method of any one of Embodiments 16-18, wherein the plurality of metal nanoparticles further comprises a plurality of substantially spherical metal nanoparticles.

[0133] Embodiment 20. The method of Embodiment 16, or any of Embodiments 16-19, wherein the metal nanoparticles comprise copper nanoparticles.

[0134] Embodiment 21. The method of Embodiment 16, or the method of any one of Embodiments 16-20, wherein the at least one surfactant comprises at least one amine surfactant.

[0135] Embodiment 22. The method of Embodiment 21, wherein the at least one amine surfactant comprises two or more amine surfactants.

[0136] Embodiment 23. The method of Embodiment 21, or the method of Embodiment 21 or Embodiment 22, wherein the at least one amine surfactant comprises one or more branched chain amines.

[0137] Embodiment 24. A method according to Embodiment 21, or a method according to any one of Embodiments 21-23, wherein when consolidating the metal nanoparticles, at least a portion of the at least one amine surfactant is removed from the metal nanoparticles below the fusion temperature of the metal nanoparticles.

[0138] Embodiment 25. A method comprising: providing a solution comprising a metal salt dissolved in an organic solvent and at least one surfactant; and adding a reducing agent to the solution at a rate sufficient to form a plurality of metal nanoparticles, wherein at least about 20% of the metal nanoparticles are plate-like nanoparticles, and the metal nanoparticles have a surfactant coating comprising at least some of the at least one surfactant; wherein the reducing agent is added at a rate sufficient to maintain the solution at a temperature of about 70°C or less while forming the metal nanoparticles.

[0139] Embodiment 26. The method of Embodiment 25, wherein the at least one surfactant comprises at least one amine surfactant.

[0140] Embodiment 27. The method of Embodiment 26, or the method of Embodiment 25 or Embodiment 26, wherein the at least one amine surfactant comprises two or more amine surfactants.

[0141] Embodiment 28. The method of embodiment 26, or the method of embodiment 26 or embodiment 27, wherein the at least one amine surfactant comprises a primary amine, a secondary amine, and a bidentate amine.

[0142] Embodiment 29. The method of Embodiment 28, wherein the secondary amine is present in a higher molar amount than the combined amount of the primary amine and the bidentate amine.

[0143] Embodiment 30. The method of embodiment 28, wherein the primary amine is present in a higher molar amount than the bidentate amine.

[0144] Embodiment 31. The method of Embodiment 26, or any of Embodiments 26-30, wherein the at least one amine surfactant comprises one or more branched chain amines.

[0145] Embodiment 32. The method according to Embodiment 25, or the method according to any one of Embodiments 25-31, further comprising: cooling the solution to room temperature within at least about 30 minutes after adding the reducing agent.

[0146] Embodiment 33. The method of any one of Embodiments 25-32, wherein at least a majority of the metal nanoparticles are plate-like nanoparticles.

[0147] Embodiment 34. The method of any one of Embodiments 25-32, or the method of any one of Embodiments 25-33, wherein at least about 80% of the metal nanoparticles are plate-like nanoparticles.

[0148] Embodiment 35. The method of any one of Embodiments 25-32, or the method of any one of Embodiments 25-34, wherein the plurality of metal nanoparticles further comprises a plurality of substantially spherical metal nanoparticles.

[0149] Embodiment 36. The method of any one of Embodiments 25-32, or the method of any one of Embodiments 25-35, wherein the metal nanoparticles comprise copper nanoparticles.

[0150] Embodiment 37. A method according to any one of Embodiments 25-32, or a method according to any one of Embodiments 25-36, wherein the plate-like nanoparticles have a longitudinal thickness ranging from about 5 nm to about 40 nm.

[0151] Embodiment 38. A method according to any one of Embodiments 25-32, or a method according to any one of Embodiments 25-37, wherein the plate-like nanoparticles have a longitudinal aspect ratio ranging from about 1 to about 100.

[0152] Embodiment 39. The method of any one of Embodiments 25-32, or the method of any one of Embodiments 25-38, wherein the plate-like nanoparticles have a maximum dimension ranging from about 10 nm to about 400 nm.

[0153] Embodiment 40. The method of any one of Embodiments 25-32, or the method of any one of Embodiments 25-39, wherein the plate-like nanoparticles have a fusion temperature ranging from about 180°C to about 240°C.

[0154] Embodiment 41. A method according to any one of Embodiments 25-32, or a method according to any one of Embodiments 25-40, wherein the reducing agent is added at a rate sufficient to maintain the solution at a temperature of about 40°C to about 70°C while forming the metal nanoparticles.

[0155] Embodiment 42. The method of any one of Embodiments 25-32, or the method of any one of Embodiments 25-41, wherein the temperature of the solution increases by about 10°C to about 15°C upon addition of the reducing agent.

[0156] Embodiment 43. The method of any one of Embodiments 25-32, or the method of any one of Embodiments 25-42, wherein no external heating is applied to the solution when forming the metal nanoparticles.

[0157] In order to facilitate a better understanding of the present disclosure, the following examples of preferred or representative embodiments are given. The following examples should in no way be construed as limiting or defining the scope of the present invention.

[0158] Example

[0159] General synthesis conditions for producing plate-like nanoparticles. Copper plate-like nanoparticles are prepared by slowly adding a reducing agent to reduce the copper salt while keeping the reaction at a temperature that forms plate-like nanoparticles. In brief, a copper metal precursor (copper salt), such as copper (II) chloride, copper (II) bromide or copper (II) sulfate, is dispersed in a glyme solvent at a concentration of 0.25-11% by weight based on the dissolved metal ions from the salt. A surfactant mixture containing one, two, three or four surfactants is then added at a molar ratio of at least 4.1:1 of total surfactant to copper metal precursor. After dissolving the copper salt and mixing thoroughly for 2-3 hours, a sufficient amount of reducing agent is slowly added over a period of 7-45 minutes to allow the temperature to exceed 35°C to form copper plate-like nanoparticles. The reaction mixture is then cooled to room temperature over a period of 20-90 minutes, and the plate-like nanoparticles are separated by centrifugation.

[0160] Specific synthesis conditions for producing plate-like nanoparticles (experimental). 4 The copper plate-like nanoparticles are prepared by slowly reducing copper (II) chloride in glyme. Specifically, a copper salt is dispersed in a glyme solvent at a concentration of at least 0.95% by weight based on the dissolved metal ions, and a surfactant mixture comprising a bidentate amine, a primary amine, and a secondary amine is added at a total molar ratio of the amine surfactant to copper of at least 5.7. The presence of each amine surfactant is such that the bidentate amine is present in the lowest molar amount and the secondary amine is present in the highest molar amount. After thorough mixing, about 1.0-1.5 equivalents of NaBH2O2 are slowly added at a steady rate relative to the dissolved metal ions over a period of at least 7 minutes. 4 The addition rate is controlled so that the temperature exceeds 35°C. The reaction mixture is then slowly cooled to room temperature over a period of at least 20 minutes and the copper plate-like nanoparticles are separated by centrifugation. The separated copper plate-like nanoparticles are washed with water and stored while still wet. The still wet product can be safely stored at room temperature in a well-sealed container for several years.

[0161] Specific synthesis conditions for producing spherical nanoparticles (comparison). 4The copper (II) chloride in glyme is rapidly reduced to prepare substantially spherical copper nanoparticles. Specifically, the copper salt is dispersed in a glyme solvent at a concentration of 0.40-0.50 wt % based on the dissolved metal ions from the copper salt, and a surfactant mixture comprising a bidentate amine, a primary amine, and a secondary amine is added at a total molar ratio of the amine surfactant to copper of at least 4.1. The presence of each amine surfactant is such that the bidentate amine and the primary amine are present in approximately equimolar amounts, and the secondary amine is present in a maximum molar amount. After thorough mixing, approximately 1.0 equivalent of NaBH2O2 is added relative to the dissolved metal ions in less than 3 minutes. 4 . At a rapid addition rate, the temperature peaks at around 45°C. The reaction mixture is then rapidly cooled to room temperature in no more than 10 minutes and the substantially spherical copper nanoparticles are isolated by centrifugation. The isolated copper plate-like nanoparticles are washed with water and stored while still wet. The still wet product can be safely stored at room temperature in a well-sealed container for several years.

[0162] Figure 7 is a bar graph of the particle size distribution obtained from a representative copper nanoparticle synthesis, in which plate-shaped nanoparticles were produced. FIG. 8A to FIG. 8D is an exemplary SEM image of copper nanoparticles produced at different reducing agent introduction rates. As shown, the size of the plate-like nanoparticles can vary significantly, and a variable number of substantially spherical copper nanoparticles can also be present in combination with the plate-like nanoparticles. In addition, the plate-like nanoparticles can present a range of semi-regular polygonal shapes. Fig.8D It is shown that plate-like nanoparticles can be easily stacked on top of each other, even in the resulting form.

[0163] The copper nanoparticles containing plate-like nanoparticles were sintered to produce a self-supporting film containing a bulk copper matrix. Briefly, the reflow (sintering) was performed at a peak temperature of 235° C. in a standard commercial convection reflow oven (e.g., produced by Heller Industries), a BTU reflow oven, a Sikama oven, etc., under an inert gas environment for a period of 4-6 minutes. For comparison, a comparative copper nanoparticle sample containing mainly substantially spherical metal nanoparticles or a 1:1 mixture of substantially spherical copper nanoparticles and plate-like nanoparticles was sintered under the same conditions. Fig. 9 is an exemplary SEM image of bulk copper formed primarily of plate-like copper nanoparticles after sintering. As shown, there is very little evidence of porosity within the film, indicating the dense packing provided by the plate-like nanoparticles. Fig. 10A is a photograph of a sintered film produced from copper nanoparticles comprising mainly plate-shaped nanoparticles. Fig. 10B is a photograph of a sintered thin film produced from a 1:1 mixture of substantially spherical copper nanoparticles and plate-shaped copper nanoparticles. Fig. 10Cis a photograph of comparative sintered films produced from copper nanoparticles containing substantially spherical metal nanoparticles. The thickness of each sintered film is 25 μm. The sintered film produced mainly from plate-shaped copper nanoparticles ( Fig. 10A ) is self-supporting, light pink, and appears to contain a substantially continuous metal layer. The film quality decreases with increasing loading of substantially spherical copper nanoparticles ( Fig. 10B ). Comparative sintered films produced from essentially spherical copper nanoparticles ( Fig. 10C ) is duller and more consistent with the bronze color of metallic copper, but is significantly more cracked and brittle than sintered films produced from plate-like nanoparticles alone. The comparative film contains multiple fused copper regions, but limited long-range integrity. The resistance of the comparative sintered film is about 4 to 30 times higher than the resistance of the sintered film produced from copper nanoparticles having primarily plate-like morphology. Depending on the thickness, the sheet resistance values ​​of the films produced from plate-like nanoparticles are about 1-3 mOhm / square and lower, while when substantially spherical metal nanoparticles are used, the sheet resistance values ​​range from 5-10 mOhm / square and higher.

[0164] Unless otherwise indicated, all numbers used in this specification and the related claims to represent the amount of ingredients, properties (such as molecular weight), reaction conditions, etc. should be understood as being modified by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters set forth in the following specification and the attached claims are approximate values, which may vary depending on the desired properties sought to be obtained by the embodiments of the present invention. At a minimum, and without attempting to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should at least be interpreted in light of the number of reported significant digits and by applying ordinary rounding techniques.

[0165] One or more exemplary embodiments of the features incorporated into the present disclosure are presented herein. For the sake of clarity, all features of physical embodiments are not described or shown in this application. It should be understood that in the development of physical embodiments in conjunction with the present disclosure, many implementation-specific decisions must be made to achieve the developer's goal, such as meeting system-related, business-related, government-related and other constraints, which vary with the implementation and change over time. Although the developer's efforts may be time-consuming, such efforts will be routine tasks for those of ordinary skill in the art and benefit from the present disclosure.

[0166] Therefore, the present disclosure is well suited for achieving the mentioned purposes and advantages and those inherent therein. The specific embodiments disclosed above are merely illustrative, as the present disclosure can be modified and practiced in different but equivalent ways, which is obvious to those skilled in the art who benefit from the teachings herein. In addition, except as described in the claims below, it is not intended to limit the details of the construction or design shown herein. Therefore, it is obvious that the specific exemplary embodiments disclosed above can be changed, combined or modified, and all such changes are considered to be within the scope and essence of the present invention. The disclosure herein can be appropriately implemented in the absence of any element not specifically disclosed herein and / or any optional element disclosed herein. Although the composition and method are described with "comprising", "containing" or "including" various components or steps, the composition and method can also be "essentially composed of various components and steps" or "composed of various components and steps". All numbers and ranges disclosed above can be changed by a certain amount. Whenever a numerical range with a lower limit and an upper limit is disclosed, any number and any included range falling within the range are specifically disclosed. Specifically, each value range disclosed herein (in the form of "about a to about b", or equivalently, "about a to b", or equivalently, "about ab") should be understood to set forth each number and range encompassed within the broader value range. In addition, the terms in the claims have their ordinary, ordinary meaning unless otherwise explicitly and clearly defined by the patentee. In addition, the indefinite articles "a" or "an" used in the claims are defined herein to mean one or more than one of the elements into which they are introduced.

Claims

1. A composition comprising: A plurality of metal nanoparticles having a surfactant coating thereon, at least about 20% of the metal nanoparticles are plate-like nanoparticles, and the surfactant coating comprises at least one surfactant.

2. The composition of claim 1, wherein at least a majority of the metal nanoparticles are plate-like nanoparticles.

3. The composition of claim 1, wherein at least about 80% of the metal nanoparticles are plate-like nanoparticles.

4. The composition of claim 1, wherein the plate-like nanoparticles have a longitudinal thickness ranging from about 5 nm to about 40 nm. 5 . The composition of claim 1 , wherein the plate-like nanoparticles have a longitudinal aspect ratio ranging from about 1 to about 100.

6. The composition of claim 1, wherein the plate-like nanoparticles have a maximum dimension ranging from about 10 nm to about 400 nm.

7. The composition of any one of claims 1-6, wherein the plurality of metal nanoparticles further comprises a plurality of substantially spherical metal nanoparticles.

8. The composition of any one of claims 1-6, wherein the metal nanoparticles comprise copper nanoparticles.

9. The composition of any one of claims 1-6, wherein the at least one surfactant comprises at least one amine surfactant.

10. The composition of claim 9, wherein the at least one amine surfactant comprises two or more amine surfactants.

11. The composition of claim 9, wherein the at least one amine surfactant comprises one or more branched chain amines.

12. The composition of any one of claims 1-6, wherein the plate-like nanoparticles have a fusion temperature ranging from about 180°C to about 240°C.

13. A nanoparticle paste comprising the composition according to any one of claims 1-6.

14. A sprayable formulation comprising the composition according to any one of claims 1 to 6.

15. An ink comprising the composition according to any one of claims 1 to 6.

16. A method comprising: Depositing the composition according to any one of claims 1 to 6 on a substrate; as well as The metal nanoparticles are consolidated to form a bulk metal matrix on the substrate.

17. The method of claim 16, wherein consolidating the metallic nanoparticles comprises heating the composition to above a fusion temperature of the metallic nanoparticles.

18. The method of claim 16, wherein the plate-like nanoparticles have a fusion temperature ranging from about 180°C to about 240°C.

19. The method of claim 16, wherein the plurality of metallic nanoparticles further comprises a plurality of substantially spherical metallic nanoparticles.

20. The method of claim 16, wherein the metal nanoparticles comprise copper nanoparticles.

21. The method of claim 16, wherein the at least one surfactant comprises at least one amine surfactant.

22. The method of claim 21, wherein the at least one amine surfactant comprises two or more amine surfactants.

23. The method of claim 21, wherein the at least one amine surfactant comprises one or more branched chain amines.

24. The method of claim 21, wherein at least a portion of the at least one amine surfactant is removed from the metal nanoparticles below a fusion temperature of the metal nanoparticles when consolidating the metal nanoparticles.

25. A method comprising: providing a solution comprising a metal salt and at least one surfactant dissolved in an organic solvent; as well as adding a reducing agent to the solution at a rate sufficient to form a plurality of metal nanoparticles, wherein at least about 20% of the metal nanoparticles are plate-shaped nanoparticles, the metal nanoparticles having a surfactant coating comprising at least some of the at least one surfactant; wherein the reducing agent is added at a rate sufficient to maintain the solution at a temperature of about 70° C. or less while forming the metal nanoparticles.

26. The method of claim 25, wherein the at least one surfactant comprises at least one amine surfactant.

27. The method of claim 26, wherein the at least one amine surfactant comprises two or more amine surfactants.

28. The method of claim 26, wherein the at least one amine surfactant comprises primary amines, secondary amines, and bidentate amines.

29. The method of claim 28, wherein the secondary amine is present in a higher molar amount than the combined amount of the primary amine and the bidentate amine.

30. The method of claim 28, wherein the primary amine is present in a higher molar amount than the bidentate amine.

31. The method of claim 26, wherein the at least one amine surfactant comprises one or more branched chain amines.

32. The method of claim 25, further comprising: After adding the reducing agent, the solution is cooled to room temperature over at least about 30 minutes.

33. The method of any one of claims 25-32, wherein at least a majority of the metal nanoparticles are plate-like nanoparticles.

34. The method of any one of claims 25-32, wherein at least about 80% of the metal nanoparticles are plate-like nanoparticles.

35. The method of any one of claims 25-32, wherein the plurality of metal nanoparticles further comprises a plurality of substantially spherical metal nanoparticles.

36. The method of any one of claims 25-32, wherein the metal nanoparticles comprise copper nanoparticles.

37. The method of any one of claims 25-32, wherein the plate-like nanoparticles have a longitudinal thickness ranging from about 5 nm to about 40 nm.

38. The method of any one of claims 25-32, wherein the plate-like nanoparticles have a longitudinal aspect ratio ranging from about 1 to about 100.

39. The method of any one of claims 25-32, wherein the plate-like nanoparticles have a largest dimension ranging from about 10 nm to about 400 nm.

40. The method of any one of claims 25-32, wherein the plate-like nanoparticles have a fusion temperature ranging from about 180°C to about 240°C.

41. The method of any one of claims 25-32, wherein the reducing agent is added at a rate sufficient to maintain the solution at a temperature of about 40°C to about 70°C while forming the metal nanoparticles.

42. The method of any one of claims 25-32, wherein the temperature of the solution increases by about 10°C to about 15°C upon adding the reducing agent.

43. The method of any one of claims 25-32, wherein no external heating is applied to the solution while forming the metal nanoparticles.

Citation Information

Patent Citations

  • Rhenium nanoparticles

    US7736414B1

  • Lead solder-free electronics

    US8105414B2

  • Tin nanoparticles and methodology for making same

    US8192866B2

  • Nanoparticle composition and methods of making the same

    US8486305B2

  • Compositions containing tin nanoparticles and methods for use thereof

    US8834747B2